MANGROVE MANAGEMENT STUDIES IN BREBES REGENCY, CENTRAL JAVA, INDONESIA - Wahyuni, Titi; Kusumaningrum, Lia; Susiyanti, Fitri (Universitas Gorontalo, 2026)
Human anthropogenic activities, such as land conversion for ponds and agriculture, as well as the development of environmentally unfriendly infrastructure, have contributed to increased environmental degradation. Furthermore, it is driving global temperature increase and climate change, including pressure on the sustainability of mangrove areas such as those in Brebes Regency, Central Java, Indonesia. This study aims to evaluate mangrove management in the Brebes Regency. The study applies qualitative and quantitative descriptive approaches (mixed methods) with the Systematic Literature Review (SLR) method and a survey method to examine the mangrove management that has been implemented. Management aspects include abiotic, biotic, and cultural aspects. The result of the study showed that the coastal ecosystem in the western region of Brebes Regency is dominated by mangrove ecosystems, where most of the mangrove areas have been converted into ponds. The study recommends providing assistance to communities regarding a green economy that supports mangrove sustainability, mitigating the damage of mangrove areas, conserving mangrove areas, and continuously implementing integrated management to ensure sustainability in the future.